Historical medicine: Biblical and talmudic surgery and surgical practice - Estēe Dvorjetski (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
The legacy of surgery in ancient Jews included those who cared for the wounds and injuries. In light of this they were awarded the title of experts, ummanim. The aim of the paper is to introduce the history of the craft of surgery from biblical times throughout the talmudic period focusing on historical and medical perspectives. Along the way, the surgical progress made a creative advancement of anatomical studies.